The Influence of Influencer Marketing and Content Quality on the Effectiveness of Climate Crisis Campaigns - Alvin Jefry; Suharjo Suharjo; Hasanah Hasanah (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
This study aims to analyse the effectiveness of digital climate crisis campaigns by integrating influencer marketing literature into the Theory of Planned Behaviour (TPB) framework. The study takes the context of IKLIM Fest in Bali, where musicians act as environmental influencers who bridge scientific narratives through musical expression. Using a quantitative approach, data was collected from 210 respondents exposed to Music Declares Emergency Indonesia (MDE Indonesia) digital activations through purposive sampling techniques, then analysed using the Structural Equation Modelling-Partial Least Squares (SEM-PLS) method. The results show that influencer marketing and content quality significantly influence behavioural intention, both directly and through the mediation of attitude, subjective norms, and perceived behavioural control. Theoretically, these findings expand the validity of the TPB model in the context of social media-based climate crisis communication and confirm the effectiveness of non-traditional communicators, particularly musicians, in encouraging public engagement. The uniqueness of this study lies in the cross-sector collaboration between the creative industry and climate activism, which has practical implications for environmental organisations in designing more authentic and impactful campaign strategies through the utilisation of public figures from the arts sector.